How Can Smoking Cessation Be Induced Before Surgery? A Systematic Review and Meta-Analysis of Behavior Change Techniques and Other Intervention Characteristics - Prestwich, Andrew; Moore, Sally; Kotze, Alwyn; Budworth, Luke; Lawton, Rebecca; Kellar, Ian (Frontiers in Psychology, 2017)
Background: Smokers who continue to smoke up to the point of surgery are at increased risk of a range of complications during and following surgery. Objective: To identify whether behavioral and/or pharmacological interventions increase the likelihood that smokers quit prior to elective surgery and which intervention components are associated with larger effects. Design: Systematic review with meta-analysis. Data sources: MEDLINE, Embase, and Embase Classic, CINAHL, CENTRAL. Study selection: Studies testing the effect of smoking reduction interventions delivered at least 24 h before elective surgery were included. Study appraisal and synthesis: Potential studies were independently screened by two people. Data relating to study characteristics and risk of bias were extracted. The effects of the interventions on pre-operative smoking abstinence were estimated using random effects meta-analyses. The association between specific intervention components (behavior change techniques; mode; duration; number of sessions; interventionist) and smoking cessation effect sizes were estimated using meta-regressions. Results: Twenty-two studies comprising 2,992 smokers were included and 19 studies were meta-analyzed. Interventions increased the proportion of smokers who were abstinent or reduced smoking by surgery relative to control: g = 0.56, 95% CI 0.32–0.80, with rates nearly double in the intervention (46.2%) relative to the control (24.5%). Interventions that comprised more sessions, delivered face-to-face and by nurses, as well as specific behavior change techniques (providing information on consequence of smoking/cessation; providing information on withdrawal symptoms; goal setting; review of goals; regular monitoring by others; and giving options for additional or later support) were associated with larger effects. Conclusion: Rates of smoking can be halved prior to surgery and a number of intervention characteristics can increase these effects. There was, however, some indication of publication bias meaning the benefits of such interventions may be smaller than estimated. Registration: Prospero 2015: CRD42015024733